2000
DOI: 10.1111/j.1469-7793.2000.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of betamethasone administration to the fetal sheep in late gestation on fetal cerebral blood flow

Abstract: Glucocorticoid administration to women at risk of preterm delivery to accelerate fetal lung maturation has become standard practice. Antenatal glucocorticoids decrease the incidence of intraventricular haemorrhage as well as accelerating fetal lung maturation. Little is known regarding side effects on fetal cerebral function. Cortisol and synthetic glucocorticoids such as betamethasone increase fetal blood pressure and femoral vascular resistance in sheep. We determined the effects of antenatal glucocorticoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
71
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 45 publications
6
71
1
Order By: Relevance
“…Adrenergic cardiovascular drive and noradrenergic infl uences play a key role in the development or progression of hypertension and the metabolic syndrome in the adult (Grassi et al, 2009), making this system another key candidate for glucocorticoid induced long-term alterations in system balance. This notion is supported by experiments showing a sustained elevation of blood pressure and altered baroreceptor heart rate response in fetal sheep and the baboon and increased central and peripheral vascular resistance after glucocorticoid administration (Derks et al, 1997;Fletcher et al, 2002;Koenen et al, 2002;Schwab et al, 2000). 6.5 HPA axis functionality in neonates after intrauterine betamethasone treatment Η 53…”
Section: Vulnerability Of the Sympathetic Nervous Systemsupporting
confidence: 58%
“…Adrenergic cardiovascular drive and noradrenergic infl uences play a key role in the development or progression of hypertension and the metabolic syndrome in the adult (Grassi et al, 2009), making this system another key candidate for glucocorticoid induced long-term alterations in system balance. This notion is supported by experiments showing a sustained elevation of blood pressure and altered baroreceptor heart rate response in fetal sheep and the baboon and increased central and peripheral vascular resistance after glucocorticoid administration (Derks et al, 1997;Fletcher et al, 2002;Koenen et al, 2002;Schwab et al, 2000). 6.5 HPA axis functionality in neonates after intrauterine betamethasone treatment Η 53…”
Section: Vulnerability Of the Sympathetic Nervous Systemsupporting
confidence: 58%
“…Fetal arterial blood pressure changes in their time course are a sensitive measure of the biological activity of glucocorticoids. [7][8][9][10][11] We hypothesized that the clinical doses of betamethasone produce supramaximal effects on the fetal cardiovascular system as an indicator that the doses used clinically may also need evaluation in relation to lung maturation. …”
mentioning
confidence: 99%
“…Fetal exposure at critical developmental stages to glucocorticoid concentrations that are inappropriate for that stage has been shown to have acute adverse effects on the central nervous [2][3][4][5][6] and cardiovascular systems in the fetal sheep and baboon. [7][8][9][10][11] In the cardiovascular system of sheep and nonhuman primates, synthetic glucocorticoids increase peripheral [7][8][9]11 and cerebral vascular resistance, 10 leading to increased mean fetal arterial blood pressure and decreased cerebral blood flow. Although the increased blood pressure may have harmful effects, the increase of cerebral vascular resistance may protect the brain from postasphyxic blood pressure peaks and intraventricular hemorrhage (Schwab M Although it has been shown in sheep that repeated treatments may be of benefit for the lung, 12 to our knowledge there has never been a study designed to examine a broad range of doses at the clinical level to determine the dose of maternal glucocorticoid that is optimal for the effects on the fetus in rodents, sheep, nonhuman primates or humans (PubMed, January 1966-January 2006; no language restrictions; search terms: antenatal or prenatal; glucocorticoids, steroids or betamethasone; dose or pharmacokinetics; lung or blood pressure).…”
mentioning
confidence: 99%
“…DM enhanced the hypoxemiainduced peripheral vasoconstriction, increasing the fetal femoral vascular resistance by 72% as compared with the salinetreated group, in which it increased by 32%. We previously demonstrated that betamethasone given directly to the fetus at 125 dGA decreases fetal cerebral blood flow and blunts hypercapnia-induced vasodilation (15). In contrast, maternal administration at this earlier gestational age seems to provide a slight increase in cortical flow.…”
mentioning
confidence: 99%
“…For instance, exogenous glucocorticoid use has been associated with reduced weight and head circumference in infants at birth (7,13,14). In addition to the effects on fetal growth, antenatal glucocorticoid treatment administered to fetal sheep in the last third of gestation increases fetal blood pressure (BP) (15)(16)(17)(18)(19). Repeated maternal betamethasone administration in sheep also suppresses neuroendocrine and adrenal responsiveness in the preterm newborn lamb (20,21).…”
mentioning
confidence: 99%